Impacts of wheat milling by-products in supplements on the intake and digestion of steers consuming low-quality forage - Farmer, C.G.; Cochran, R.C.; Simms, D.D.; Heldt, J.S.; Mathis, C.P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixteen ruminally fistulated steers were used to evaluate the effects of feeding supplements containing combinations of two wheat-milling by-products on forage intake, digestibility, and ruminal characteristics. The by-products accounted for 47 to 49% of each supplement and were as follows: 1) 100% wheat bran; 2) 67% wheat bran, 33% second clears; and 3) 33% wheat bran, 67% second clears. All supplements contained about 30% CP. Compared with unsupplemented controls, forage intake and digestibility were significantly higher for supplemented steers. However, no differences occurred among by-product treatments. In conclusion, if the protein content is adequate, the choice of bran (high digestible fiber) vs. second clears (high starch) has little impact on forage use.
Keywords: Beef; Steers; Forage; Intake; Digestion; Wheat by-products